ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP TERJADINYA FINANCIAL DISTRESS PERUSAHAAN MANUFAKTUR DI INDONESIA - Nindi Rustyaningrum; Abdul Rohman (Diponegoro Journal of Accounting, 2021)
This research was conducted to examine the effect of corporate governance of the financial distress. Variables used in the examination are managerial ownership, institutional ownership, size board, board independency, board activity and audit committee knowledge as the independent variables, also financial distress as the dependent variable. The samples of this research is a manufacturing companies listed in Indonesian Stock Exchange from 2017 – 2019. The samples based on purposive sampling method with certain criteria(s). Based on the criteria the samples obtained 232 data. The method used is hypothesis testing by using mutiple linear regression test. The result showed that managerial ownership, institutional ownership, size board, board independency, and board activity not affect the financial distress. Meanwhile, audit committe knowledge have a negative and signifikan on financial distress.